2016
DOI: 10.1074/jbc.m116.753145
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Promotes Antibody-mediated Fratricide of Acute Myeloid Leukemia Cells

Abstract: Edited by Peter CresswellAcute myeloid leukemia (AML) is characterized by the proliferation of immature myeloid lineage blasts. Due to its heterogeneity and to the high rate of acquired drug resistance and relapse, new treatment strategies are needed. Here, we demonstrate that IFN␥ promotes AML blasts to act as effector cells within the context of antibody therapy. Treatment with IFN␥ drove AML blasts toward a more differentiated state, wherein they showed increased expression of the M1-related markers HLA-DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…Interestingly, the levels of CD38 protein expression on NK cells and the magnitude of regulation upon Dara binding appear to be different among different donors (see Fig.3C), an effect that brings us to speculate that differences in the immune system of patients may be critical for the deepness of response to Dara, a hypothesis that will need further validation. In agreement with previous data, which have shown a pivotal role of Dara in inducing macrophage-mediated phagocytosis; 33,34 our results demonstrate specifically that direct NK cell activation by Dara induces monocyte activation and polarization, increasing the ability of this subpopulation to kill cancer cells. The macrophage T cell activation markers CD80/CD86, which were upregulated upon Dara treatment via NK cell activation, play a pivotal role not only for macrophage polarization but also as a critical costimulatory molecule in the initial step of T cell activation and survival, 35 through its binding to the T cell receptor CD28, a hypothesis that is fully consistent with what is observed in Dara-treated patients, as recently reported.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the levels of CD38 protein expression on NK cells and the magnitude of regulation upon Dara binding appear to be different among different donors (see Fig.3C), an effect that brings us to speculate that differences in the immune system of patients may be critical for the deepness of response to Dara, a hypothesis that will need further validation. In agreement with previous data, which have shown a pivotal role of Dara in inducing macrophage-mediated phagocytosis; 33,34 our results demonstrate specifically that direct NK cell activation by Dara induces monocyte activation and polarization, increasing the ability of this subpopulation to kill cancer cells. The macrophage T cell activation markers CD80/CD86, which were upregulated upon Dara treatment via NK cell activation, play a pivotal role not only for macrophage polarization but also as a critical costimulatory molecule in the initial step of T cell activation and survival, 35 through its binding to the T cell receptor CD28, a hypothesis that is fully consistent with what is observed in Dara-treated patients, as recently reported.…”
Section: Discussionsupporting
confidence: 93%
“…Primary cell handling was done as described previously. [ 22 ] White blood cells apheresed from AML patients were obtained after written informed consent in accordance with the Declaration of Helsinki under a protocol approved by the institutional review board of The Ohio State University. Cells were stored in liquid nitrogen in 20% FBS and 10% DMSO until needed for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…They also showed that IFN-γ treatment promotes the myeloid differentiation and phagocytic activity of primary AML patient cells. The combination of IFN-γ and FCγR activation enhanced the production of granzyme B, suggesting that IFN-γ can induce AML cells to differentiate into immune effector cells ( 46 ).…”
Section: Type II Ifn (Ifn-γ)mentioning
confidence: 99%